Method for preparing polymeric ferric sulfate by using titanium white waste acid concentrated residue
Patent Information
- Application Number
- CN202310051821.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-02-02
AI Technical Summary
1、该方法以的副产物一水硫酸亚铁和废酸为原料,但一水硫酸亚铁为钛白粉副产物七水硫酸亚铁经升温转晶、离心分离、高温干燥后所得,原料价格高昂且不易得
1、本发明所述制备聚合硫酸铁的方法主要包括六个步骤,其中,
Smart Images

Figure CN116022857B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyferric sulfate preparation technology, specifically to a method for preparing polyferric sulfate using concentrated residue from titanium dioxide waste acid. Background Technology
[0002] Titanium dioxide waste acid concentrate residue is a byproduct of the titanium dioxide industry, produced in extremely large quantities; approximately one ton of concentrate residue is generated for every ton of titanium dioxide produced. The main component of the concentrate residue is ferrous sulfate, and it also contains impurities such as sulfuric acid, metatitanic acid, and heavy metal ions (including calcium, magnesium, chromium, and manganese). However, due to the stringent requirements for these impurities in industries involving ferrous sulfate, the concentrate residue has been difficult to utilize effectively.
[0003] Currently, in the phosphorus removal agent industry, polyferric sulfate is usually prepared by using concentrated residue. However, due to the high acid content in the concentrated residue, the basicity of the resulting polyferric sulfate is low, resulting in poor phosphorus removal effect. Furthermore, due to the influence of impurities such as metatitanic acid, the produced polyferric sulfate is prone to precipitation and has a short shelf life.
[0004] Furthermore, patent document CN109928434A discloses a method for preparing polyferric sulfate, a water treatment agent, from ferrous sulfate monohydrate, a byproduct of titanium dioxide production, and waste acid. This method uses ferrous sulfate monohydrate and waste acid as raw materials and can efficiently and rapidly produce first-grade polyferric sulfate with a small amount of catalyst. However, in practical applications, this method still has the following technical problems: 1. This method uses ferrous sulfate monohydrate, a byproduct of titanium dioxide, and waste acid as raw materials. However, ferrous sulfate monohydrate is obtained by heating and crystallizing ferrous sulfate heptahydrate, a byproduct of titanium dioxide, followed by centrifugal separation and high-temperature drying. The raw materials are expensive and difficult to obtain.
[0005] 2. This method uses waste acid generated during the production of titanium dioxide as raw material. However, this waste acid contains a large amount of impurities such as chromium, manganese, and titanium. The polyferric sulfate produced without impurity removal treatment has a high impurity content, resulting in poor performance.
[0006] 3. The polyferric sulfate synthesized by this method has not undergone sedimentation treatment with a coagulant aid, resulting in a high content of suspended solids in the produced polyferric sulfate, which can easily cause pipe blockage during use. Summary of the Invention
[0007] The purpose of this invention is to overcome the above-mentioned technical problems existing in the prior art and to provide a method for preparing polyferric sulfate using titanium dioxide waste acid concentrate residue. In the preparation process, this invention can remove impurity elements such as lead, chromium, and manganese from the raw materials and can cause the solid suspended matter in the polyferric sulfate to form flocs and settle. This not only reduces the solid suspended matter content in the finished polyferric sulfate but also improves the quality of the polyferric sulfate. At the same time, the use of titanium dioxide waste acid concentrate residue as the main raw material makes the raw materials readily available and low in cost.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue, characterized by comprising the following steps: Step 1: Take the concentrated residue of titanium dioxide waste acid and mix it with the waste acid before titanium dioxide concentration to obtain the waste acid concentrated residue slurry; Step 2: Centrifuge the waste acid concentrate slurry to obtain dry-based waste acid concentrate slurry; Step 3: Mix the dry-based waste acid concentrate residue with industrial water to obtain ferrous slurry; Step 4: Add a cleansing agent to the ferrous slurry, stir and mix well to remove heavy metal ions from the ferrous slurry; Step 5: The purified ferrous slurry is introduced into the polyferric sulfate synthesis reactor and synthesized by catalytic oxidation to obtain a polyferric sulfate mixture; Step 6: Add a coagulant to the polyferric sulfate synthesis reactor, and after standing and settling, obtain a polyferric sulfate solution.
[0009] In step 1, the waste acid before titanium dioxide concentration is the waste dilute sulfuric acid generated during the water washing process in the preparation of titanium dioxide by the sulfuric acid method. The waste acid before titanium dioxide concentration contains 20-25% H2SO4 and 2-5% Fe. The waste acid concentration residue is the filter residue generated during the waste acid concentration process in the preparation of titanium dioxide by the sulfuric acid method. The waste acid concentration residue contains 15-20% H2SO4 and 15-20% Fe, and the iron-acid ratio is 0.75-1.33.
[0010] In step 1, the mass ratio of titanium dioxide waste acid concentrate residue to titanium dioxide waste acid before concentration is 1:1-1:4, and the stirring and mixing conditions are 10-200 rpm at a temperature of 10℃-90℃ for 10-120 min.
[0011] In step 2, the centrifugation time for the waste acid concentrate slurry is 10s-120s, and the iron-to-acid ratio in the dry waste acid concentrate slurry after centrifugation is 1.5-2.0.
[0012] In step 3, the total amount of iron ions in the ferrous slurry is 10%-12%, and the specific gravity of the ferrous slurry is 1.4g / ml-1.6g / ml.
[0013] In step 4, the impurity remover is one of sodium sulfide, ammonium sulfide, or potassium sulfide, or a mixture of several in any proportion, and the amount of impurity remover added is 0.05%-5%.
[0014] In step 4, the ferrous slurry and the impurity remover are mixed at a stirring rate of 10-200 rpm and a temperature of 10℃-90℃ for 30-180 min.
[0015] In step 5, the feed temperature of the polyferric synthesis reactor is 20-70℃, the oxidant is oxygen, the catalyst is sodium nitrite, and the catalyst addition amount is 0.5-0.8 kg / t.
[0016] In step 6, the coagulant is one of anionic polyacrylamide, cationic polyacrylamide, or nonionic polyacrylamide, or a mixture of several in any proportion, and the amount of coagulant added is 0.005%-0.05%.
[0017] In step 6, the mixing temperature of the coagulant aid and the polyferric sulfate mixture is 10℃-120℃, and the settling time is 10-180min.
[0018] The advantages of using this invention are: 1. The method for preparing polyferric sulfate according to the present invention mainly includes six steps, wherein, Step 1 uses titanium dioxide waste acid concentrate residue and waste acid before titanium dioxide concentration as raw materials to prepare waste acid concentrate residue slurry. Its advantages are that it can increase the concentration of sulfuric acid in waste acid before titanium dioxide concentration and save energy consumption for waste acid concentration. At the same time, it can also adjust the titanium dioxide waste acid concentrate residue to a suitable ferric acid ratio so that it can be directly used for the synthesis of polyferric sulfate. The operation is simple and conducive to the resource utilization of titanium dioxide waste acid concentrate residue.
[0019] Step 2 involves centrifuging the waste acid concentrate slurry, which has the advantage of increasing the dry basis ferric acid ratio and enabling automated continuous production.
[0020] Step 3 involves mixing the dry-based waste acid concentrate residue with industrial water. The advantage of this method is that it allows for control of the final product's specific gravity and reduces production costs.
[0021] Step 4 involves adding a decontaminant to the ferrous slurry. The advantage of this step is that it can remove heavy metals from the raw materials, thereby improving the quality of the finished product.
[0022] Step 5 involves catalytic oxidation in a polyferric synthesis reactor. The advantage of this step is that it can reduce the cost of using oxidants and increase the oxidation rate.
[0023] Step 6 uses a coagulant to help the solid suspended matter in the polyferric sulfate mixture form flocs, which has the advantage of accelerating the settling speed and further improving product quality.
[0024] 2. In step 1, the present invention further specifies the content of H2SO4, Fe content and ferric acid ratio of titanium dioxide waste acid concentrate residue and waste acid before titanium dioxide concentration. The advantage is that it controls the basicity of the finished product and improves the effect of the product in wastewater treatment.
[0025] 3. The mixing method of titanium dioxide waste acid concentration residue and titanium dioxide waste acid before concentration in this invention is simple and helps to reduce production costs.
[0026] 4. The present invention limits the centrifugation time of the waste acid concentrate slurry to 10s-120s. Since the longer the centrifugation time, the lower the sulfuric acid content in the dry basis, the ferric acid ratio can be controlled by controlling the centrifugation time in practical applications, thereby realizing the automatic and continuous production of the product.
[0027] 5. By limiting the total amount and specific gravity of ferrous ions in the ferrous slurry, this invention can control the iron content in the finished product, thereby improving the product's effectiveness in wastewater treatment.
[0028] 6. This invention can use sodium sulfide, ammonium sulfide or potassium sulfide as impurity removal agent, which has the advantages of low cost and good impurity removal effect.
[0029] 7. The conditions for mixing the ferrous slurry and the impurity removal agent in this invention are relatively simple, and it has the advantages of short reaction time and low production cost.
[0030] 8. The polyacrylamide used in this invention has excellent coagulation aid effect, which can remove solid suspended matter in the polyferric sulfate mixture and improve product quality.
[0031] 9. The present invention sets the mixing temperature of the coagulant and polyferric sulfate mixture to 10℃-120℃ and the settling time to 10-180min. This allows the high temperature of the synthesized polyferric sulfate itself to be utilized without the need for additional cooling equipment, which helps to reduce production costs.
[0032] 10. This invention uses waste acid before titanium dioxide concentration as a washing agent for titanium dioxide waste acid concentration residue. It does not participate in the synthesis of polyferric sulfate. Washing the titanium dioxide waste acid concentration residue with waste acid before titanium dioxide concentration can increase the concentration of titanium dioxide waste acid and reduce the energy consumption of titanium dioxide production enterprises in the later stage of waste acid concentration. Attached Figure Description
[0033] Figure 1 This is a flowchart of the present invention. Detailed Implementation
[0034] This invention provides a method for preparing polyferric sulfate using concentrated residue from titanium dioxide waste acid, such as... Figure 1 As shown, it includes the following steps: Step 1: Take titanium dioxide waste acid concentrate residue and titanium dioxide waste acid before concentration in a mass ratio of 1:1-1:4 and stir them in a mixing tank. The stirring conditions are 10-200 rpm at a temperature of 10℃-90℃ for 10-120 min. In this invention, a more preferred stirring condition is 10-100 rpm at a temperature of 20℃-30℃ for 10-30 min. After mixing, waste acid concentrate residue slurry is obtained.
[0035] It should be noted that the waste acid before titanium dioxide concentration is the waste dilute sulfuric acid (washing mother liquor) generated during the water washing process in the preparation of titanium dioxide by the sulfuric acid method. The H2SO4 content in the waste acid before titanium dioxide concentration is 20-25%, and the Fe content is 2-5%. The waste acid concentration residue of titanium dioxide is the filter waste residue generated during the waste acid concentration process in the preparation of titanium dioxide by the sulfuric acid method. The H2SO4 content in the waste acid concentration residue of titanium dioxide is 15-20%, the Fe content is 15-20%, and the iron-acid ratio (the ratio of iron ions to acid ions) is 0.75-1.33.
[0036] Step 2: The waste acid concentrate slurry is introduced into a vertical centrifuge for centrifugal separation. The centrifugation time is 10s-120s. After centrifugation, the dry basis waste acid concentrate slurry is removed, and the ferric acid ratio is controlled at 1.5-2.0. The filtrate after centrifugation can be returned to the titanium dioxide production line. In this invention, a more preferred centrifugation time is 15s-30s, and a more preferred ferric acid ratio is 1.6-1.7.
[0037] It should be noted that the ferric acid ratio can be controlled by adjusting the centrifugation time. The longer the centrifugation time, the lower the sulfuric acid content in the dry-based waste acid concentrate residue, and the higher the ferric acid ratio.
[0038] Step 3: Add the dry-based waste acid concentrate residue to a ferrous slurry tank, add industrial water, and mix to obtain a ferrous slurry. In this invention, the total amount of iron ions in the ferrous slurry is 10%-12%, and the specific gravity is 1.4g / ml-1.6g / ml; more preferably, the total amount of iron ions is 11.0%-11.5%, and the specific gravity is 1.50g / ml-1.55g / ml.
[0039] Step 4: Add a decontaminant to the ferrous slurry. The decontaminant is one of sodium sulfide, ammonium sulfide, or potassium sulfide, or a mixture of several in any proportion. The amount of decontaminant added is 0.05%-5%, and more preferably 0.1%-1.0%.
[0040] Then, stir at a stirring rate of 10-200 rpm at a temperature of 10℃-90℃ for 30-180 min, or more preferably, stir at a stirring rate of 10-100 rpm at a temperature of 20℃-30℃ for 60-90 min. After stirring and mixing, remove heavy metal ions from the ferrous slurry.
[0041] Step 5: Introduce the purified ferrous slurry into the polyferric sulfate synthesis reactor. The feed temperature of the polyferric sulfate synthesis reactor is 20-70℃. Then, sodium nitrite is used as a catalyst and oxygen is used as an oxidant. The catalyst is added at a rate of 0.5-0.8 kg / t, and the polyferric sulfate mixture is obtained through catalytic oxidation synthesis.
[0042] Step 6: Add a coagulant aid to the polyferric sulfate synthesis reactor. The coagulant aid used in this invention is one of anionic polyacrylamide, cationic polyacrylamide, or nonionic polyacrylamide, or a mixture of several in any proportion. The amount of coagulant aid added is 0.005%-0.05%, more preferably 0.01%-0.02%. The polyferric sulfate mixture and the coagulant aid are mixed at a temperature of 10℃-120℃. After mixing, the mixture is allowed to stand for sedimentation for 10-180 minutes, thus obtaining a polyferric sulfate solution (clear liquid) in the polyferric sulfate storage tank. In this invention, the more preferred mixing temperature for the polyferric sulfate mixture and the coagulant aid is 80℃-100℃, and the more preferred standing sedimentation time is 60-90 minutes.
[0043] Because the present invention removes impurities such as lead, chromium, and manganese from the raw materials through a purification agent during the preparation process, and causes the solid suspended matter in the polyferric sulfate mixture to form flocs and settle through a coagulant, it not only reduces the content of solid suspended matter in the finished polyferric sulfate, but also improves the quality of polyferric sulfate.
[0044] The present invention will be further described in detail below with reference to specific embodiments.
[0045] Example 1 A method for preparing polyferric sulfate using titanium dioxide waste acid concentrate residue and waste acid before titanium dioxide concentration as raw materials includes the following steps: Step 1: Take titanium dioxide waste acid concentrate residue and titanium dioxide waste acid before concentration in a 1:1 mass ratio and stir them in a mixing tank. The stirring conditions are 10 rpm and 10℃ for 10 minutes. After the mixing is completed, waste acid concentrate residue slurry is obtained.
[0046] Step 2: Introduce the waste acid concentrate slurry into a vertical centrifuge for centrifugal separation. The centrifugation time is 10 seconds. After centrifugation, remove the dry waste acid concentrate slurry and control the iron-acid ratio to be 1.5.
[0047] Step 3: Add the dry-based waste acid concentrate residue into the ferrous slurry tank, add industrial water, and mix to obtain ferrous slurry. The total amount of iron ions in the ferrous slurry is 10%, and the specific gravity is 1.4 g / ml.
[0048] Step 4: Add sodium sulfide as a decontaminant to the ferrous slurry. The amount of sodium sulfide added is 0.05%. Then stir at a stirring speed of 10 rpm at a temperature of 10°C for 30 minutes. After stirring and mixing, remove heavy metal ions from the ferrous slurry.
[0049] Step 5: The purified ferrous slurry is introduced into the polyferric sulfate synthesis reactor at a feed temperature of 20°C. Sodium nitrite is then used as a catalyst and oxygen as an oxidant. The catalyst is added at a rate of 0.5 kg / t, and the polyferric sulfate mixture is obtained through catalytic oxidation.
[0050] Step 6: Add anionic polyacrylamide as a coagulant aid to the polyferric sulfate synthesis reactor at a concentration of 0.005%. Mix the polyferric sulfate mixture with the coagulant aid at 10°C. After mixing, allow it to stand for 10 minutes to settle, thus obtaining a polyferric sulfate solution (clear liquid) in the polyferric sulfate storage tank.
[0051] In this embodiment, the final polyferric sulfate solution was also tested according to the test method specified in GB / T14591-2016. The polyferric sulfate indexes were: TFe=10.02%, basicity=9.85%, and specific gravity=1.43g / ml, which proves that this method can obtain a product with better quality.
[0052] Example 2 A method for preparing polyferric sulfate using titanium dioxide waste acid concentrate residue and waste acid before titanium dioxide concentration as raw materials includes the following steps: Step 1: Mix titanium dioxide waste acid concentrate residue and titanium dioxide waste acid before concentration in a mixing tank at a mass ratio of 1:3. The mixing conditions are 100 rpm and 50°C for 60 minutes. After mixing, waste acid concentrate residue slurry is obtained.
[0053] Step 2: Introduce the waste acid concentrate slurry into a vertical centrifuge for centrifugal separation. The centrifugation time is 60 seconds. After centrifugation, remove the dry basis waste acid concentrate slurry and control the iron-acid ratio to be 1.75.
[0054] Step 3: Add the dry-based waste acid concentrate residue into the ferrous slurry tank, add industrial water, and mix to obtain ferrous slurry. The total amount of iron ions in the ferrous slurry is 11%, and the specific gravity is 1.5 g / ml.
[0055] Step 4: Add ammonium sulfide as a removal agent to the ferrous slurry. The amount of ammonium sulfide added is 2%. Then stir at a stirring speed of 100 rpm at a temperature of 50°C for 90 minutes. After stirring and mixing, remove heavy metal ions from the ferrous slurry.
[0056] Step 5: The purified ferrous slurry is introduced into the polyferric sulfate synthesis reactor at a feed temperature of 45°C. Sodium nitrite is then used as a catalyst and oxygen as an oxidant. The catalyst is added at a rate of 0.65 kg / t, and the polyferric sulfate mixture is obtained through catalytic oxidation.
[0057] Step 6: Add cationic polyacrylamide, a coagulant aid, to the polyferric sulfate synthesis reactor at a concentration of 0.01%. Mix the polyferric sulfate mixture with the coagulant aid at 60°C. After mixing, allow it to stand for 90 minutes to settle, thus obtaining a polyferric sulfate solution (clear liquid) in the polyferric sulfate storage tank.
[0058] In this embodiment, the final polyferric sulfate solution was also tested according to the test method specified in GB / T14591-2016. The polyferric sulfate indexes were: TFe=10.90%, basicity=12.95%, and specific gravity=1.51g / ml, which proves that this method can obtain a product with better quality.
[0059] Example 3 A method for preparing polyferric sulfate using titanium dioxide waste acid concentrate residue and waste acid before titanium dioxide concentration as raw materials includes the following steps: Step 1: Mix titanium dioxide waste acid concentrate residue and titanium dioxide waste acid before concentration in a mixing tank at a mass ratio of 1:4. The mixing conditions are 200 rpm and 90°C for 120 min. After mixing, waste acid concentrate residue slurry is obtained.
[0060] Step 2: Introduce the waste acid concentrate slurry into a vertical centrifuge for centrifugal separation. The centrifugation time is 120s. After centrifugation, remove the dry basis waste acid concentrate slurry and control the iron-acid ratio to 2.0.
[0061] Step 3: Add the dry-based waste acid concentrate residue into the ferrous slurry tank, add industrial water, and mix to obtain ferrous slurry. The total amount of iron ions in the ferrous slurry is 12%, and the specific gravity is 1.6 g / ml.
[0062] Step 4: Add potassium sulfide as a decontaminant to the ferrous slurry. The amount of potassium sulfide added is 5%. Then stir at a stirring speed of 200 rpm at a temperature of 90°C for 180 min. After stirring and mixing, remove heavy metal ions from the ferrous slurry.
[0063] Step 5: The purified ferrous slurry is introduced into the polyferric sulfate synthesis reactor at a feed temperature of 70°C. Sodium nitrite is then used as a catalyst and oxygen as an oxidant. The catalyst is added at a rate of 0.8 kg / t, and the polyferric sulfate mixture is obtained through catalytic oxidation.
[0064] Step 6: Add nonionic polyacrylamide as a coagulant to the polyferric sulfate synthesis reactor at a concentration of 0.05%. Mix the polyferric sulfate mixture with the coagulant at 120°C. After mixing, allow it to stand for 180 minutes to settle, thus obtaining a polyferric sulfate solution (clear liquid) in the polyferric sulfate storage tank.
[0065] In this embodiment, the final polyferric sulfate solution was also tested according to the test method specified in GB / T14591-2016. The polyferric sulfate indexes were: TFe=12.252%, basicity=15.56%, and specific gravity=1.60g / ml, which proves that this method can obtain a product with better quality.
[0066] Example 4 A method for preparing polyferric sulfate using titanium dioxide waste acid concentrate residue and waste acid before titanium dioxide concentration as raw materials includes the following steps: Step 1: Take titanium dioxide waste acid concentrate residue and titanium dioxide waste acid before concentration in a 1:2 mass ratio and stir them in a mixing tank. The stirring conditions are 80 rpm and 25°C for 20 minutes. After mixing, waste acid concentrate residue slurry is obtained.
[0067] Step 2: Introduce the waste acid concentrate slurry into a vertical centrifuge for centrifugal separation. The centrifugation time is 20 seconds. After centrifugation, remove the dry waste acid concentrate slurry and control the iron-acid ratio to be 1.65.
[0068] Step 3: Add the dry-based waste acid concentrate residue into the ferrous slurry tank, add industrial water, and mix to obtain ferrous slurry. The total amount of iron ions in the ferrous slurry is 11.2%, and the specific gravity is 1.52 g / ml.
[0069] Step 4: Add a scavenging agent, which is a mixture of sodium sulfide and potassium sulfide, to the ferrous slurry at a concentration of 0.5%. Then stir at 80 rpm at 25°C for 80 minutes to remove heavy metal ions from the ferrous slurry.
[0070] Step 5: The purified ferrous slurry is introduced into the polyferric sulfate synthesis reactor at a feed temperature of 50°C. Sodium nitrite is then used as a catalyst and oxygen as an oxidant. The catalyst is added at a rate of 0.6 kg / t, and the polyferric sulfate mixture is obtained through catalytic oxidation.
[0071] Step 6: Add a coagulant aid to the polyferric sulfate synthesis reactor. The coagulant aid is a mixture of anionic and cationic polyacrylamide, and the addition amount is 0.015%. The polyferric sulfate mixture and the coagulant aid are mixed at a temperature of 90°C. After mixing, the mixture is allowed to stand for 80 minutes to settle, and a polyferric sulfate solution (clear liquid) is obtained in the polyferric sulfate storage tank.
[0072] In this embodiment, the final polyferric sulfate solution was also tested according to the test method specified in GB / T14591-2016. The polyferric sulfate indexes were: TFe=11.35%, basicity=12.0%, and specific gravity=1.51g / ml, which proves that this method can obtain a product with better quality.
[0073] The above description is merely a specific embodiment of the present invention. Any feature disclosed in this specification may be replaced by other equivalent or similar features unless otherwise specified. All features or steps in the disclosed methods or processes may be combined in any way, except for mutually exclusive features and / or steps.
Claims
1. A method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue, characterized in that... Includes the following steps: Step 1: Take the concentrated residue of titanium dioxide waste acid and mix it with the waste acid before titanium dioxide concentration to obtain a slurry of concentrated residue of waste acid; the waste acid before titanium dioxide concentration is the waste dilute sulfuric acid generated in the water washing process during the preparation of titanium dioxide by the sulfuric acid process, and the content of H2SO4 in the waste acid before titanium dioxide concentration is 20-25%, and the content of Fe is 2-5%; the concentrated residue of titanium dioxide waste acid is the filter waste residue generated in the waste acid concentration process during the preparation of titanium dioxide by the sulfuric acid process, and the content of H2SO4 in the concentrated residue of titanium dioxide waste acid is 15-20%, the content of Fe is 15-20%, and the iron-acid ratio is 0.75-1.33; Step 2: Centrifuge the waste acid concentrate slurry to obtain dry-based waste acid concentrate; the centrifugation time is 10s-120s, and the ferric acid ratio in the dry-based waste acid concentrate after centrifugation is 1.5-2.0; Step 3: Mix the dry-based waste acid concentrate residue with industrial water to obtain ferrous slurry; Step 4: Add a decontaminant to the ferrous slurry, stir and mix well to remove heavy metal ions from the ferrous slurry; the decontaminant is one of sodium sulfide, ammonium sulfide or potassium sulfide or several mixed in any proportion; Step 5: The purified ferrous slurry is introduced into the polyferric sulfate synthesis reactor and synthesized by catalytic oxidation to obtain a polyferric sulfate mixture; Step 6: Add a coagulant to the polyferric sulfate synthesis reactor, and after standing and settling, obtain a polyferric sulfate solution; the coagulant is one of anionic polyacrylamide, cationic polyacrylamide, or nonionic polyacrylamide, or a mixture of several in any proportion.
2. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 1, the mass ratio of titanium dioxide waste acid concentrate residue to titanium dioxide waste acid before concentration is 1:1-1:4, and the stirring and mixing conditions are 10-200 rpm at a temperature of 10℃-90℃ for 10-120 min.
3. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 3, the total amount of iron ions in the ferrous slurry is 10%-12%, and the specific gravity of the ferrous slurry is 1.4g / ml-1.6g / ml.
4. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 4, the amount of impurity remover added is 0.05%-5%.
5. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 4, the ferrous slurry and the impurity remover are mixed at a stirring rate of 10-200 rpm and a temperature of 10℃-90℃ for 30-180 min.
6. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 5, the feed temperature of the polyferric synthesis reactor is 20-70℃, the oxidant is oxygen, the catalyst is sodium nitrite, and the catalyst addition amount is 0.5-0.8 kg / t.
7. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 6, the amount of coagulant added is 0.005%-0.05%.
8. The method for preparing polyferric sulfate from titanium dioxide waste acid concentrate residue according to claim 1, characterized in that: In step 6, the mixing temperature of the coagulant aid and the polyferric sulfate mixture is 10℃-120℃, and the settling time is 10-180min.
Citation Information
Patent Citations
Method for preparing polyferric sulfate from ferrous sulfate monohydrate and waste acids
CN109928434A
Recycling method and device for ferrous sulfate monohydrate serving as titanium dioxide factory byproduct
CN110540247A
Method for producing polyferric sulfate by using naturally oxidized and deteriorated ferrous sulfate as raw material
CN113955808A